2017
DOI: 10.1016/j.carbon.2017.07.094
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid effects in graphene oxide/carbon nanotube-supported layered double hydroxides: enhancing the CO2 sorption properties

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Graphene oxide (GO) and multi-walled carbon nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Summary of different support materials for the preparation of LDH‐based catalysts: (a) TiO 2 @LDH, (b) LDH/CNT, (c) LDH/GO, and (d) Co 3 O 4 @LDH …”
Section: Advancements Of Tm‐based Electrocatalystsmentioning
confidence: 99%
“…Summary of different support materials for the preparation of LDH‐based catalysts: (a) TiO 2 @LDH, (b) LDH/CNT, (c) LDH/GO, and (d) Co 3 O 4 @LDH …”
Section: Advancements Of Tm‐based Electrocatalystsmentioning
confidence: 99%
“…In addition, the energy efficiency of these sorption systems needs to be further improved so they can be environmentally and economically feasible compared to more mature technologies. [ 33 ]…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that significant performance enhancements of LDH‐derived MMOs in both organosulfur and CO 2 sorption can be obtained by dispersing them on high surface area materials, such as carbons. [ 28,33b,34 ] It has also been shown that graphene‐based powders (such as GO) provide particularly suitable supports due to matching morphology and surface charge between LDH and GO support. [ 28,34 ] However, there are no studies assessing the benefits of 3D‐structured macroscopic graphene supports, such as rGO aerogels, on the MMO performance in these important sorption applications.…”
Section: Introductionmentioning
confidence: 99%
“…used LDHs as catalysts to produce CNTs. Marco et al . have supported graphene oxide and CNTs over LDHs for CO 2 adsorption applications.…”
Section: Introductionmentioning
confidence: 99%